2016
DOI: 10.1038/nature20099
|View full text |Cite
|
Sign up to set email alerts
|

Break-induced telomere synthesis underlies alternative telomere maintenance

Abstract: Homology-directed DNA repair is essential for genome maintenance through templated DNA synthesis. Alternative lengthening of telomeres (ALT) necessitates homology-directed DNA repair to maintain telomeres in about 10–15% of human cancers. How DNA damage induces assembly and execution of a DNA replication complex (break-induced replisome) at telomeres or elsewhere in the mammalian genome is poorly understood. Here we define break-induced telomere synthesis and demonstrate that it utilizes a specialized replisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
444
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(472 citation statements)
references
References 35 publications
27
444
1
Order By: Relevance
“…Of note, the same study also elucidates the molecular steps that rescue the degraded forks upon drug withdrawal by showing that the initial resection of the regressed arm generates a reversed fork with a 3′-ssDNA tail that is then cleaved by MUS81 to permit POLD3-dependent rescue of the stalled forks in a BRCA2-deficient background (Figure 2B). Interestingly, a similar mechanism was recently proposed for completion of DNA replication at common fragile sites and telomeric loci (Dilley et al, 2016; Minocherhomji et al, 2015). This mechanism relies on a specialized form of DNA repair originally characterized in yeast and termed break-induced replication (BIR), whereby MUS81 cleavage of stalled replication forks produces a migrating bubble that drives POLD3-dependent DNA synthesis (Sakofsky and Malkova, 2017).…”
mentioning
confidence: 61%
“…Of note, the same study also elucidates the molecular steps that rescue the degraded forks upon drug withdrawal by showing that the initial resection of the regressed arm generates a reversed fork with a 3′-ssDNA tail that is then cleaved by MUS81 to permit POLD3-dependent rescue of the stalled forks in a BRCA2-deficient background (Figure 2B). Interestingly, a similar mechanism was recently proposed for completion of DNA replication at common fragile sites and telomeric loci (Dilley et al, 2016; Minocherhomji et al, 2015). This mechanism relies on a specialized form of DNA repair originally characterized in yeast and termed break-induced replication (BIR), whereby MUS81 cleavage of stalled replication forks produces a migrating bubble that drives POLD3-dependent DNA synthesis (Sakofsky and Malkova, 2017).…”
mentioning
confidence: 61%
“…Therefore, these replication problems may also initiate break-induced replication (BIR)-mediated DNA replication processes at the telomere region in ALT cells (55), leading to a preference for lagging strands. We also showed that ATRX depletion partially contributes to preferential elongation in lagging strands (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…This is dependent upon the inherent ability of these factors to stimulate non-sister chromosome interactions. The ALT pathway operates via a recombination-mediated mechanism in which, in the absence of normal telomerase-mediated elongation, telomeres behave like a broken chromosome end, serving to stimulate RAD51 recombinasemediated strand invasion of an uncapped telomere into a nonsister telomere to enable the invading end to serve as a substrate for DNA replication-dependent de novo telomere elongation (35). This phenomenon can not only help drive tumor formation but also enables tumor cell proliferative activity and is likely to contribute to tumor cell evolutionary potential (36,37), although this latter point requires experimental exploration.…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%